ETHANOL EXTRACT OF Moringa oleifera INCREASED THE NUMBER OF SPERMATOZOA AND IMPROVED SPERM MORPHOLOGY OF OLD Rattus norvegicus - Luh Putu Widiastini (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Aging in men can lead to decreased semen volume, abnormal sperm morphology, and decreased sperm motility. This study aims to determine the effect of ethanol extract of moringa (Moringa oleifera) leaf on the number and morphology of spermatozoa in old Wistar rats (Rattus norvegicus). This study used healthy old rats, 18–19 months old, with a bodyweight of 200–250 g and no physical disabilities. The 36 rats were divided into 2 groups, i.e. the treatment group (fed with ethanol extract of moringa leaves 50 mg/kgBW/0.5 mL CMC 0.5% every day) and the control group (0.5 mL CMC 0.5% every day) for 30 days. The results showed that moringa leaf ethanol extract increased the number of spermatozoa (p-value 0.000) and improved spermatozoa morphology (p-value 0.000). It can be concluded that the ethanol extract of moringa leaves significantly increased the number and improved the morphology of the spermatozoa in the aged rats.